HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN HASIL KECEPATAN LARI 40 METER PADA SISWA KELAS V SDN 004 SALO KECAMATAN SALO KABUPATEN KAMPAR - Mursa, Em Waidila; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the researcher’s observation of Students in class V SDN 004 Salo District Of Kampar. Researcher found the low of phsycal condition of student, also there are some students in the current running position of the body is not skewed. The purpose of this research is to see correlation power of leg muscles with the 40 meter running speedresult of student in class V SDN 004 Salo district of Kampar. Population in this research are 24 people, 14 people from Va 10 people from Vb. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 24 people. Research instrument is measured the power of leg muscles used leg dynamometer and 40 meter running speed test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is correlation the power of leg with 40 meter running speed , which shows correlation rhitung = 0,465>rtabel = 0,413Key word : The power of leg muscles, 40 meter running speed.